Reproduksi Kemiskinan Nelayan Kecil di Kabupaten Timor Tengah Utara, Provinsi Nusa Tengara Timur (Studi Kasus di Desa Oesoko, Kecamatan Insana Utara) - Petrus Suse Kobesi; Marsianus Falo; Oktavianus Tabenu; Windi Bunga Devita (AGRIMOR, 2023)
. Poverty is a phenomenon that is often encountered, one of which is in the social groups of small fishing communities. This is a manifestation of the fishermen's inability to meet the economic needs of their lives. This study aims to examine the reproduction of poverty in small fishermen in Oesoko Village, North Insana District by using qualitative descriptive analysis methods. The technique of determining the research location used was purposive sampling and for the determination of informants using the survey method. The primary data and secondary data used in this study, primary data were obtained from respondents through the questionnaires provided, in-depth interviews using the provided guidelines and secondary data obtained from relevant agencies. The results of the analysis show that the reproduction of the impoverishment of small fishermen in Oesoko Village, North Central Timor Regency is caused by several factors including structural factors such as access to capital for fishing business development, government policies to provide fishing technology assistance, patron clients and access to markets. Cultural factors include the lack of financial management of small fishermen's households, customs that are quite burdensome and the behavior patterns of small fishing communities that are still consumptive. The factor of Human Capital (Human Capital) is still low so that it affects the mindset and behavior in making decisions